2021
DOI: 10.1021/acsami.1c05824
|View full text |Cite
|
Sign up to set email alerts
|

Domain Engineered Lead-Free Ceramics with Large Energy Storage Density and Ultra-High Efficiency under Low Electric Fields

Abstract: Dielectric energy storage materials are becoming increasingly popular due to their potential superiority, for example, excellent pulse performance as well as good fatigue resistance. Although numerous studies have focused on lead-free dielectric materials which possess outstanding energy storage characteristics, the results are still not satisfying in terms of achieving both large discharging energy density (W d) and high discharging efficiency (η) under low electric fields, which is crucial to be conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(34 citation statements)
references
References 68 publications
3
28
1
Order By: Relevance
“…22 Band C 1 and C 2 in the 500–600 cm −1 wavenumber region are intimately associated with BO 6 octahedra vibrations. 23,24 Fig. S4 (ESI†) displays the evolution of the wavenumber and intensity ratio of the two modes.…”
Section: Resultsmentioning
confidence: 99%
“…22 Band C 1 and C 2 in the 500–600 cm −1 wavenumber region are intimately associated with BO 6 octahedra vibrations. 23,24 Fig. S4 (ESI†) displays the evolution of the wavenumber and intensity ratio of the two modes.…”
Section: Resultsmentioning
confidence: 99%
“…12,107 From a microscopic perspective, the shape evolution of P-E loops is closely linked with the dynamic response of PNRs, which has been observed in lead-free RFE materials. 20,108,109 To validate the domain evolution in the BNT-BAT-CT ceramics, outof-plane PFM phase, amplitude, and morphology characterization studies in scanning areas of 5 Â 5 mm 2 at a voltage of 20 V and different relaxation times are employed, as shown in Fig. 5(e)-(j), S15 and S16, † respectively.…”
Section: (B)mentioning
confidence: 99%
“…It can be clearly observed that the Raman bands between 200 and 700 cm −1 move to higher wavenumbers according to the deconvolution results, which means a strengthening of the bonding between cations and oxygen, indicating the increment of the unit cell polarity. 22,35,39 The Raman spectra and the XRD refinement both verify the polarization enhancement behavior with increasing BNT content.…”
Section: Resultsmentioning
confidence: 72%
“…Unlike the mainstream way of destroying long-range ferroelectric/antiferroelectric order to improve energy-storage properties, we have selected the end members with high P max gene to promote the polarization behavior of SBT-based ceramics. Above all, BNT end member with large P max is chosen on account of the 6s 2 lone pair electron configuration . Furthermore, we add Bi­(Mg 0.5 Ti 0.5 )­O 3 end member simultaneously possessing A-site and B-site cation displacements that is beneficial for the ferroelectricity of perovskite structure .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation